Optical Vortices In Wavelength Division Multiplexed Passive Optical Networks - Angela Amphawan; Yousef Ali Fazea Al-Nadesh; Kashif Nisar (International Institute for Science, Technology and Education, 2012)
Wavelength division multiplexing passive optical network (WDM –PON) is being widely considered for the deployment of fiber-to-the-home (FTTH) to deliver broadband access to business and home users. Optical vortices are helical wavefronts which focus to rings, rather than central points. This important property makes optical vortices ideal for exciting higher-order modes where manufacturing defects in the multimode fiber core such as tips and dips are less dominant and modes have closer propagation times. This research presents the application of VCSEL arrays for the independent transmission of parallel data streams over optical vortices in multimode fiber to increase the degrees of freedom in a FTTH WDM-PON. VCSEL arrays are selected for multiplexing optical vortices in WDM-PONs as they are tunable, compact, individually addressable and inexpensive. This book presents the mathematical framework and simulation of the novel design. A transmission speed of 40Gbps is achieved at a central wavelength of 1550.12 nm while maintaining a BER of less than 1 x 10-9. The analysis reveals important results that should be considered by operators towards the success of FTTH.